Pembelajaran Pendidikan Agama Islam berbasis Blended Learning di Sekolah Menengah Atas - Dwiputro, Retna Maskur (Tawazun: Jurnal Pendidikan Islam, 2022)
The application of ICT in education has given birth to new learning models in the learning system, such as: learning which is usually limited to classrooms with a predetermined schedule, developing flexibly anywhere and anytime on website applications (e-learning), as well as materials learning which is usually presented using material facilities such as printed books, whiteboards which are developed into electronic devices by utilizing computer technology and internet networks. The mixed/blended model places the online delivery system as an integral part of the overall learning process. That is, the face-to-face and online learning process is a unified whole. The purpose of the study was to analyze blended learning in Islamic Religious Education subjects at SMA PGRI 3 Bogor City. The research method uses qualitative methods with the type of field research. Sources of data were obtained from observations, documentation, and in-depth interviews as well as Focus Group Discussions (FGD) by relevant Education Personnel, other Education Personnel who teach PAI at the school, and Education Personnel in the Curriculum section. The results of this study: (1) The application of the blended learning learning model has been going well because the learning carried out is a combination of face-to-face/virtual and online (e-learning). (2) The learning model used is only one learning model, namely discovery learning. (3) Applied learning uses various combinations of approaches, namely: scientific approach and contextual approach. (4) The combination is also carried out in learning methods, namely: lecture method, discussion method, question and answer method, and brainstorming method. (5) Likewise, the learning resources used also vary, be it educators, PAI books, PPT, PDF, internet, Quizizz, and other relevant references. Abstrak Penerapan TIK dalam pendidikan telah melahirkan model-model pembelajaran baru dalam sistem pembelajaran, seperti: pembelajaran yang biasanya terbatas pada ruang kelas dengan jadwal yang telah ditentukan, berkembang secara fleksibel di mana saja dan kapan saja pada aplikasi website (e-learning), serta bahan pembelajaran yang biasanya disajikan dengan menggunakan fasilitas materi seperti buku cetak, papan tulis yang dikembangkan menjadi perangkat elektronik dengan memanfaatkan teknologi komputer dan jaringan internet. Model mixed/blended, menempatkan sistem penyampaian online sebagai bagian integral dari keseluruhan proses pembelajaran. Artinya, proses pembelajaran tatap muka dan online merupakan satu kesatuan yang utuh. Tujuan dari penelitian untuk menganalisis pembelajaran blended learning pada mata pelajaran Pendidikan Agama Islam di SMA PGRI 3 Kota Bogor. Metode penelitian menggunakan metode kualitatif dengan jenis field research. Sumber data diperoleh dari observasi, dokumentasi, dan wawancara mendalam serta Focus Group Discussion (FGD) oleh Tenaga Pendidikan yang terkait, Tenaga Pendidikan lain yang mengajar PAI di sekolah tersebut, dan Tenaga Kependidikan bagian Kurikulum. Hasil dari penelitian ini: (1) Penerapan model pembelajaran blended learning sudah berjalan dengan baik karena pembelajaran yang dilakukan merupakan kombinasi tatap muka/virtual dan online (e-learning). (2) Model pembelajaran yang digunakan hanya satu model pembelajaran yaitu discovery learning. (3) Pembelajaran terapan menggunakan berbagai kombinasi pendekatan, yaitu: pendekatan saintifik dan pendekatan kontekstual. (4) Kombinasi juga dilakukan dalam metode pembelajaran, yaitu: metode ceramah, metode diskusi, metode tanya jawab, dan metode brainstorming. (5) Demikian pula sumber pembelajaran yang digunakan juga bervariasi, baik itu pendidik, buku PAI, PPT, PDF, internet, Quizizz, dan referensi lain yang relevan.